What influences the intention of farmers to use green organic fertilizer? Introducing green awareness into the theory of planned behavior - Sha Lou; Xiaoxin Zhang; Dehua Zhang (Ciência Rural, 2024)
ABSTRACT: China is the biggest muskmelon producing country across the world. Extreme application of fertilizer during planting of muskmelon poses a serious threat to the environment and food safety, so how to promote farmers to use organic fertilizer has become an important topic. This study creatively introduced green awareness into the extended framework of theory of planned behavior to explore the decisive factors of muskmelon farmers’ behavior intention to apply green organic fertilizer. The structural equation model is used for investigating behavior intention of 543 muskmelon farmers in Leting County, China. The results suggested that both subjective norm and green awareness can affect muskmelon farmers’ behavior intention positively and significantly. When the subjective norm increases by 1 standard deviation, the farmers’ intention increases by 1.028 standard deviation; for every 1 standard deviation increase in green awareness, the farmers’ intention increased by 0.703 standard deviation.